Evaluation of product support sources - Mosier, Joseph (Kansas State University, 2014)
Companies must weigh the trade-offs of support strategies and choose between the effectiveness of meeting customer expectations and the cost of implementing product support tools and services. These support strategies can be critical to the success of a company and therefore, must provide efficient problem resolution in order to meet the satisfaction of the customer and retailer. This thesis reviews survey data collected from a large agricultural equipment company’s retailers on their satisfaction of product support tools and services provided by the company, and how the retailers utilize these product support tools and services when attempting to resolve a product issue. This evaluation of a company’s product support strategy leads to the identification of potential solutions to help maximize the efficiency of the problem resolution process, as well as minimize the opportunity costs and financial costs of product support sources.
Keywords: Dealer survey; Satisfaction; Product support